Marketing Kansas Sunflower - Nelson, Mark (My University, 1993)
This publication answers some basic questions and concerns regarding sunflower marketing. It briefly describes sunflower markets and then discusses deliverable grades and quality specifications, and the types of sales available to Kansas producers.
L887_1993-09
Keywords: L887; Crops; L